Farmer-friendly delivery of veterinary services: Experimental insights from the Kenyan dairy sector - Kevin W. Maina; Martin C. Parlasca; Elizaphan J. O. Rao; Matin Qaim (Journal of Agricultural Economics, 2024)
Poor health conditions of livestock cause sizeable losses for many farmers in the Global South. Veterinary services, including vaccinations, could help but often fail to reach farmers under typical smallholder conditions. Here, we examine how the provision of a vaccine against East Coast Fever (ECF)—a tick-borne disease affecting cattle in Africa—can be designed to reduce typical adoption barriers. Using data from a choice experiment with dairy farmers in Kenya, we evaluate farmers' preferences and willingness to pay for various institutional innovations in vaccine delivery, such as a stronger role of dairy cooperatives, new payment modalities with a check-off system, vaccination at farmers' homestead, and bundling vaccinations with discounts for livestock insurance. Our data reveal that farmers' awareness of the ECF vaccine is limited and adoption rates are low, largely due to institutional constraints. Results from mixed logit and latent class models suggest that suitable institutional innovations—tailored to farmers' heterogeneous conditions—could significantly increase adoption. This general finding likely also holds for other veterinary technologies and services in the Global South.
Keywords: 630; animal health; cooperatives; dairying; East Coast Fever